Oxygen thermomigration in acceptor-doped perovskite. Issue 18 (19th April 2017) - Shin, Donghoon; Yoo, Han-Ill
Abstract : The recent practice with q O * = Δ H m > 0 in treating O-thermomigration in memristive oxides is absolutely not the case. For the case of memristive perovskite CaTi0.90 Sc010 O2.95+ δ, its mobile oxygen turns from thermophilic ( q O * < 0) to thermophobic ( q O * > 0) as the minority electronic carrier type shift from electrons to holes with increasing oxygen activity. Abstract : The recent proposal of possible oxygen-thermomigration as a plausible mechanism for unipolar resistive switching of oxide memristors is now widely employed in modelling or simulating their memristive function on the grounds of the conventional picture that the mobile component O is always thermophobic, with its reduced heat-of-transport being equal to its migrational enthalpy ( q O * = Δ H m > 0). At 1000 °C, we measured the thermomigration of mobile-component O in a prototype memristive perovskite, CaTi0.90 Sc0.10 O2.95+ δ, across its near-stoichiometric regime ( δ ≈ 0), where oxygen vacancy concentration is essentially fixed by doping acceptor impurities ( i.e., ). It has been found that the reduced heat-of-transport of mobile O ( q O *) varies systematically in the range of −2 < q O */eV ≤ +2, as the composition varies from hypo-( δ < 0) to hyper-stoichiometry ( δ > 0), exhibiting a sign reversal or thermomigration direction change from thermophilic ( q O * < 0) to thermophobic ( q O * > 0). This sign-reversal is attributed to the change in the electronic ambipolar company of from electrons to holes crossing the stoichiometric composition δ = 0. The numerical data for q O * together with the measurement details are reported.